The Infrastructure of Transphobic Feminism: A Digital Ethnography of an Anti-Trans Forum - Davis, Benjamin Clay; Cotter, Kelley (AoIR Selected Papers of Internet Research, 2026)
The rise in anti-transgender legislation and violence over the 2020s has made addressing transphobic ideologies increasingly pertinent. This paper outlines an on-going digital ethnography of the anti-trans feminist forum Ovarit, asking what affects, discourses, and desires are produced through the socio-technical relations infrastructured on the forum? We are specifically interested in how anti-trans feminists routinize and legitimize their worldview through the relations and interactions afforded by the sites material design. This study is framed through a Black feminist theoretical lens to remain attentive to the ways race structures gender within anti-trans feminist discourse. Methodologically we first employed a walkthrough of the site to gather data on the structural design and ideological positioning of the forum as constructed by its creators. Following this we are conducting an on-going digital ethnography. This involves engaging with the forum as a non-participatory lurker, i.e., as someone who is heavily engaged with the forum on a daily basis but does not post or comment. Our preliminary findings indicate users posts are primarily interested in sharing instances of alleged trans misdeeds, either by linking to news articles or sharing anecdotes. The repetition and volume of these trans-antagonistic posts creates an environment where trans lives are deemed unlivable in public or private life. Future work will extend these initial findings, plotting out the particular patterns of user interactions. This research will contribute to existing studies exploring online bigotry and explore how anti-trans feminist rhetoric becomes materialized online.